(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Vehicle-to-Everything (V2X) communication has emerged as a cornerstone technology for intelligent transportation systems, enabling real-time data exchange between vehicles, infrastructure, and pedestrians. The FR1 frequency band, as defined in 5G New Radio (NR), offers significant potential for low-latency and high-reliability V2X applications. This paper presents the design, optimization, and performance evaluation of a compact FR1 band antenna tailored for low-latency V2X communication. The proposed antenna utilizes a novel geometrical configuration to achieve wide impedance bandwidth, high radiation efficiency, and stable gain across the FR1 spectrum. Detailed simulations are conducted to optimize key antenna parameters, followed by prototype fabrication and experimental validation. The results demonstrate that the antenna provides excellent return loss characteristics, omnidirectional radiation patterns suitable for vehicular deployment, and minimal latency impact, making it highly suitable for real-time V2X applications. Comparative analysis with existing FR1 antennas indicates significant improvements in bandwidth efficiency, signal integrity, and overall V2X system performance. This work contributes a practical antenna solution for next-generation connected vehicles, supporting safer and more efficient transportation networks.